2008
DOI: 10.1016/j.visres.2008.07.016
|View full text |Cite
|
Sign up to set email alerts
|

A novel GCAP1(N104K) mutation in EF-hand 3 (EF3) linked to autosomal dominant cone dystrophy

Abstract: The GUCA1A gene encodes a guanylate cyclase-activating protein (GCAP1) that is involved in regulation of phototransduction in the vertebrate retina. We discovered a novel C312A transversion in exon 2 of the human GUCA1A gene, replacing Asn-104 (N104) in GCAP1 with Lys (K), in two affected members of a family with dominant cone dystrophy. The mutation N104K is located in the third EF hand motif (EF3) shown previously to be instrumental in converting Ca2+-free GCAP1 to a GC inhibitor in the Ca2+-bound form. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 52 publications
5
39
1
Order By: Relevance
“…Incomplete suppression of GC activity at high Ca 2+ concentration was also observed with other GCAP1 mutants (p.Tyr99Cys, p.Asn104Lys, p.Ile143AsnThr, p.Leu151Phe, and p.Glu155Gly, Dizhoor, et al, 1998;Sokal, et al, 1998;Jiang, et al, 2008;Nishiguchi, et al, 2004;Sokal, et al, 2005; pointing to the importance of an exactly balanced cGMP synthesis for undisturbed vision.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Incomplete suppression of GC activity at high Ca 2+ concentration was also observed with other GCAP1 mutants (p.Tyr99Cys, p.Asn104Lys, p.Ile143AsnThr, p.Leu151Phe, and p.Glu155Gly, Dizhoor, et al, 1998;Sokal, et al, 1998;Jiang, et al, 2008;Nishiguchi, et al, 2004;Sokal, et al, 2005; pointing to the importance of an exactly balanced cGMP synthesis for undisturbed vision.…”
supporting
confidence: 53%
“…So far, only seven putative pathogenic mutations in the GUCA1A gene have been reported in patients with adCD, adCRD or adMD: p.Pro50Leu, p.Tyr99Cys, p.Asn104Lys, p.Thr114Ile, p.Ile143delinsAsnThr, p.Leu151Phe, and p.Glu155Gly (Dizhoor, et al, 1998;Downes, et al, 2001;Jiang, et al, 2005;Michaelides, et al, 2005;Nishiguchi, et al, 2004;Sokal, et al, 2005;Jiang et al, 2008. Here we report the identification of three novel and one previously published GUCA1A gene mutations in patients with adCD and adCRD.…”
Section: Introductionmentioning
confidence: 58%
“…GUCA1A (GCAP1) and GUCA1B (GCAP2), located on chromosome 6p21.1, are both required for normal phototransduction. 10,[27][28][29][30][31] They are expressed in both photoreceptor types, but GCAP1 is predominantly present in cones, and GCAP2 is more abundant in rods. 32 GU-CA1C (GCAP3) was discovered in human retina and is exclusively expressed in cones; however, no mutations in GUCA1C have been associated with retinal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rods that survived transient light damage in albino rat exhibited earlier-than-normal recovery (Wen 2008; Wen and Kraft 2008). Contrary to shortened rod recovery in RP, prolonged rod photoresponse recovery was observed in a type of cone dystrophy associated with GCAP1 mutations (Jiang et al 2008). In this study, we found that CRD caused by ABCA4 mutations ( T sat = 523 and 499 ms) is not associated with either shortened or elongated rod photoresponse recovery.…”
Section: 4 Discussionmentioning
confidence: 99%